Analisis Tipe - Tipe Kesalahan Siswa Menyelesaikan Soal Matriks Kelas X SMK Prawira Marta Kartasura - Nugroho, Tri Adi; , Dra. Nining Setyaningsih, M.Si (2015)
The purpose of this research to know types and factors that cause students to solve problems error matrix of class X Accounting SMK Prawira Marta Kartasura. This research is a qualitative research with mixed methods research design (mixed methods) using tringulasi design type. Subjects were interviewed as many as 5 students were taken from students who do a lot of errors in that classroom at most make a error that class X AK. Methods of data collection using tests, observations, interviews, and documentation. Data analysis technique is done through three stages, namely data reduction, data presentation, and conclusion. From the data obtained by the analysis of student answers and interviews show that (1) the errors done mathematically students in solving a matrix is a communication error, a error to apply the formula, and error when calculating. (2) the percentage of errors made students in solving a matrix, namely mathematical communication errors committed students to interpret the language question into the ordinary language by 22%, errors to apply the formula that made the students in using the wrong concept to resolve the matter by 50 %, and errors made when calculating the student at the time of surgery numbers by 51% (3) factors that cause students errors namely students do not understand the questions well, students either do not understand the concepts that will be used, and the student has not mastered the number operations. Keywords: error factor, qualitative, error type, tringulasi, about the matrix